Mental Health 2017: Implementing the Five Year Forward View. Issue 4 (27th November 2017) - David, Felix
Abstract : At the Mental Health 2017: Implementing the Five Year Forward View conference held in September 2017 at the Royal Society of Medicine, delegates were informed on the current government plans to focus attention on perinatal and children's mental health, to bring mental health care from institutions into the community and integrate physical and mental health services. Felix David here reports on some of the conference highlights.